Drug-related problems among type 2 diabetic patients in Sunwal Municipality of Western Nepal. - Sushma Chapagain; Nabin Pathak; Kushal Subedi; Prakash Ghimire; Bijay Adhikari; Niranjan Shrestha; Nim Bahadur Dangi (PLoS ONE)
Background Several diseases co-exist with diabetes such as hypertension, and dyslipidemia, leading to cases of non-adherence, several drug interactions, and an increased risk of adverse drug reactions among patients, which are often termed as drug-related problems (DRPs). The role of pharmacists in high-income countries is well-defined in identifying DRPs among type 2 diabetes patients. However, these roles still need to be explored within low- and middle-income countries. The study aimed to identify DRPs in Type 2 diabetic patients. Methods A community-based cross-sectional study was conducted in the Sunwal Municipality, Lumbini Province, Nepal from April to November 2021 where a stratified random sampling technique was employed to collect the data. The study included patients aged ≥ 18 years of either gender with type 2 diabetes who were prescribed at least one anti-diabetic medication. Patients were visited at their homes once identified through the community pharmacies, and a prescription review was conducted to identify the DRPs by using the Pharmaceutical Care Network Europe (PCNE) V8.02 tool and pertinent guidelines. Results Among 182 patients, 97 (53.3%) had DRPs. Most of the patients were 50-60 years (n = 46; 25.3%), with a mean ± SD age of 55.43±14.46, as most were female (n = 94; 51.6%). Biguanides and sulfonylureas were the common classes of drugs prescribed. The major class of drug associated with DRPs were biguanides (n = 85; 49.7%), followed by sulfonylureas (n = 42; 24.6%). Metformin was the major drug associated with DRPs (n = 85; 49.4%). The major type of DRP identified was treatment effectiveness (n = 82; 79.61%), while patients not adhering to drug therapy (n = 97; 71.85%) was the leading cause of DRPs. DRPs were significantly associated with the duration of diabetes (p = .007) and the number of fruit servings (p = .007). Conclusion The majority of the patients were found to have DRPs. The visiting patients at home by the pharmacists helped in identifying the DRPs and associated factors among type 2 diabetes patients, which may aid in the prevention and management of the disease.